Unexpected relevant role of gene mosaicism in patients with primary immunodeficiency diseases - Mensa-Vilaró, Anna; Bravo García-Morato, María; de la Calle-Martin, Oscar; Franco-Jarava, Clara; Martínez-Saavedra, María Teresa; González-Granado, Luis I; González-Roca, Eva; Fuster, Jose Luis; Alsina, Laia; Mutchinick, Osvaldo M; Balderrama-Rodríguez, Angélica; Ramos, Eduardo; et al. (Journal of allergy and clinical immunology, 2019)
BACKGROUND: Postzygotic de novo mutations lead to the phenomenon of gene mosaicism. The 3 main types are called somatic, gonadal, and gonosomal mosaicism, which differ in terms of the body distribution of postzygotic mutations. Mosaicism has been reported occasionally in patients with primary immunodeficiency diseases (PIDs) since the early 1990s, but its real involvement has not been systematically addressed. OBJECTIVE: We sought to investigate the incidence of gene mosaicism in patients with PIDs. METHODS: The amplicon-based deep sequencing method was used in the 3 parts of the study that establish (1) the allele frequency of germline variants (n = 100), (2) the incidence of parental gonosomal mosaicism in families with PIDs with de novo mutations (n = 92), and (3) the incidence of mosaicism in families with PIDs with moderate-to-high suspicion of gene mosaicism (n = 36). Additional investigations evaluated body distribution of postzygotic mutations, their stability over time, and their characteristics. RESULTS: The range of allele frequency (44.1% to 55.6%) was established for germline variants. Those with minor allele frequencies of less than 44.1% were assumed to be postzygotic. Mosaicism was detected in 30 (23.4%) of 128 families with PIDs, with a variable minor allele frequency (0.8% to 40.5%). Parental gonosomal mosaicism was detected in 6 (6.5%) of 92 families with de novo mutations, and a high incidence of mosaicism (63.9%) was detected among families with moderate-to-high suspicion of gene mosaicism. In most analyzed cases mosaicism was found to be both uniformly distributed and stable over time. CONCLUSION: This study represents the largest performed to date to investigate mosaicism in patients with PIDs, revealing that it affects approximately 25% of enrolled families. Our results might have serious consequences regarding treatment and genetic counseling and reinforce the use of next-generation sequencing-based methods in the routine analyses of PIDs.
Keywords: vysoce účinné nukleotidové sekvenování; alely; Gene Frequency; Female; High-Throughput Nucleotide Sequencing; frekvence genu; syndromy imunologické nedostatečnosti; rodina; ženské pohlaví; Alleles; mužské pohlaví; Humans; lidé; Male; mozaicismus; Family; Mosaicism; Immunologic Deficiency Syndromes